Antidiabetic drugs and blood pressure changes. (November 2020) - Ilias, Ioannis; Thomopoulos, Costas; Michalopoulou, Helena; Bazoukis, George; Tsioufis, Costas; Makris, Thomas
Graphical abstract: Abstract: New era antidiabetic drugs are characterized by cardiovascular safety, including specific outcome benefits observed in randomized clinical trials (RCTs). It has been postulated that the favorable effects of new antidiabetic agents are related both to better control of blood pressure (BP) levels and to activation of multiple anti-atherosclerotic properties. In this review, we aimed to assess whether antidiabetic drugs have a pressor effect in glucose control and outcome-oriented RCTs, and to summarize the activated pathophysiological mechanisms relevant to BP control following the use of different antidiabetic drug classes. We also tried to determine which, if any, are the BP-lowering effects of more intense vs less intense glucose-lowering strategy irrespectively of trial antidiabetic regimen. To provide more robust results and evidence-based argumentation, a meta-analysis of placebo-controlled antidiabetic drug RCTs was undertaken to estimate the ongoing BP reduction for all considered and each separate drug class alone. This quantitative synthesis might be helpful for the clinician 1) to select or avoid the use of some classes of antidiabetic agents with a potential favorable or adverse pressor effect, respectively 2) to organize the overall drug regimen in patients with diabetes mellitus and minimize side effects because of concomitant use of drugs with established pressor effect (i.e. antihypertensive agents). This review was also organized to indicate whether BP change associated with different antidiabetic treatments may explain the specific macrovascular outcome benefits. Between all antidiabetic drugs including exogenous insulin, only sodium-glucose cotransporter 2 inhibitors produce a clinically important BP-lowering effect, but this BP reduction alone cannot explain the observed cardiovascular benefit.